Recovery Lignin And Its Fouling Study Using Nanofiltration - Ismail, Anis Farhain (Universiti Sains Malaysia, 2017)
The recovery of lignin is particularly important because it has many applications and membrane technology has been investigated as the basis of innovative recovery solutions. The lignin recovery was studied by using nanofiltration and commercialized Dow membrane is used. A few parameter were used to analyze the lignin filtration which were feed pressure, lignin concentration and pH values of lignin solution. The rejection of lignin increased as the feed pressure increased. The highest rejection was 99.49% occurred at feed pressure of 6 bar. The concentration of lignin were varied to 10 mg/L, 100 mg/L and 1000 mg/L to investigate the relation to lignin rejection. The lowest rejection of lignin occurred during filtration of 10 ppm of lignin solution which was 70.09%. Recovery of lignin also studied at different pH which were acid (pH 4), neutral (pH 7) and base (pH 9). The physicochemical properties of lignin at different pH value also studied. The pH tolerance of various types of membranes can vary widely. Membrane lignin rejection performance depends on pH value. During filtration at pH 9, the rejection was the highest which was 99.47%. The fouling of membrane has been investigated throughout the study. The membrane fouling give effect to the efficiency of lignin rejection.